2000
DOI: 10.1038/oby.2000.14
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity, Socioeconomic Status, and Ethnicity on the Weight Status of Adolescents

Abstract: MCMURRAY, ROBERT G., JOANNE S. HARRELL, SHIBING DENG, CHYRISE B. BRADLEY, LORI M. COX, AND SHRIKANT I. BANGDIWALA. The influence of physical activity, socioeconomic status, and ethnicity on the weight status of adolescents. Obes Res. 2000;8: 130 -139. Objective: This study examined the effects of physical activity, television viewing, video game play, socioeconomic status (SES), and ethnicity on body mass index (BMI). Research Methods and Procedures:The sample was 2389 adolescents, 10 to 16 years of age (12.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
144
7
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(177 citation statements)
references
References 30 publications
14
144
7
12
Order By: Relevance
“…Larger samples could have shown statistically significant sex differences. These differences have been observed in other studies (Guillaume et al, 1997;McMurray et al, 2000;Wagner et al, 2004;Kettaneh et al, 2005), which suggest that contributory factors leading to obesity may be different in girls and boys.…”
Section: Discussionsupporting
confidence: 47%
“…Larger samples could have shown statistically significant sex differences. These differences have been observed in other studies (Guillaume et al, 1997;McMurray et al, 2000;Wagner et al, 2004;Kettaneh et al, 2005), which suggest that contributory factors leading to obesity may be different in girls and boys.…”
Section: Discussionsupporting
confidence: 47%
“…[53][54][55] Null findings are not uncommon. 56,57 One study found that obese youth are more active than nonobese youth. 58 Two recent cross-sectional studies, however, illustrate the variety of findings: BMI was negatively associated with physical activity in females, but not males, 59 whereas fat mass was negatively associated with physical activity in males, but not females.…”
Section: Physical Activity and The Development Of Obesitymentioning
confidence: 99%
“…89 Such null findings are also common. 40,57,90,91 We found two case-control studies in our review of the literature, which were essentially crosssectional in design. Television was significantly related to obesity in a case-control study of 223 obese 7-10-y-old children and controls in Sao Paulo.…”
Section: Physical Inactivity and The Development Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…This gradient has been observed in both men and women, although the association has been weaker and less consistent in men (Sobal & Stunkard, 1989). These results have been observed with both educational level and occupation as the basis for social class, and in different age groups (Wamala et al, 1997;Ball et al, 2000;Lahmann et al, 2000;McMurray et al, 2000;Rosmond & Björntorp, 2000;Van Lenthe et al, 2000;Wardle et al, 2002).…”
Section: Introductionmentioning
confidence: 92%